-3(8x+11)=6(-4x-(13))

Simple and best practice solution for -3(8x+11)=6(-4x-(13)) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(8x+11)=6(-4x-(13)) equation:


Simplifying
-3(8x + 11) = 6(-4x + -1(13))

Reorder the terms:
-3(11 + 8x) = 6(-4x + -1(13))
(11 * -3 + 8x * -3) = 6(-4x + -1(13))
(-33 + -24x) = 6(-4x + -1(13))

Multiply -1 * 13
-33 + -24x = 6(-4x + -13)

Reorder the terms:
-33 + -24x = 6(-13 + -4x)
-33 + -24x = (-13 * 6 + -4x * 6)
-33 + -24x = (-78 + -24x)

Add '24x' to each side of the equation.
-33 + -24x + 24x = -78 + -24x + 24x

Combine like terms: -24x + 24x = 0
-33 + 0 = -78 + -24x + 24x
-33 = -78 + -24x + 24x

Combine like terms: -24x + 24x = 0
-33 = -78 + 0
-33 = -78

Solving
-33 = -78

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 7=(10-g)/-2 | | 5m-12=27 | | (x-4)*y=200 | | 3x^2-41+110=0 | | 10x-60= | | (2+5i)+(-1+5i)= | | b/12-100=25 | | x/-3=11 | | 6x-1=5x-6 | | 9t-10=17-9t | | 5+w/8=30 | | 4r+5s-16r+3s= | | 32+4t-t=40 | | 1/2+t-2=-3/2 | | 6q-12=35 | | 0=t+[-14] | | 3.3=40w | | x/3e | | 3x^2+44x+96=0 | | y-60=-8.50(x-20) | | 24=m+37 | | -4x+3(2x+12)=18 | | 6x+2y=-7 | | 2x+10/3+x-10/4=9/2 | | 3x^2+19x-154=0 | | 76=6x+2(4x+3) | | 1.2x+.3x=-6 | | 3w-2+2w=-18 | | (w+5)(w-7)= | | 4x-5=8x-2 | | 12(+3y)= | | 4x+18=3(x+3) |

Equations solver categories